Design and Verifi cation of Real-Time Simulation System for Protocol Design and Performance Evaluation of Large-Scale Satellite Network - Qixuan CAO; Yan SHI; Lianwei ZHOU; Xinwang DING (天地一体化信息网络)
Aiming at the problems above, a real-time network simulation test system named SiT4NET was studied and developed.Firstly, SiT4NET used container technique to solved the problem of large-scale network node deployment with limited resources on the basis of ensuring nodes’ independence, thus improved the resource utilization of the simulation system.Secondly, the packet transmission between nodes based on data units and the mechanism for requesting/retrieving system-level data units were innovatively proposed to provided a strong foundation for real-time network simulation.And thirdly, through the standard high-level protocol interface, internal packet format and reconfi gurable mechanism of packet processing, SiT4NET reduced the complexity of conversion between the simulation implementation of the protocol and the target platform.Finally, by set up the same satellite network environment on SiT4NET and OPNET platforms, set up multiple groups of simulation scenarios, compared and analyzed the results, it showed that this method could met the performance requirements of large-scale satellite network.